The cumulative characteristics of PAEs in PM2.5 in Changji, Northwest China. (3rd July 2020) - Liu, Yuyan; Ji, Caiye; Fu, Bo; Yu, Yongxin; Liu, Haofeng; Shen, Yaxing
ABSTRACT: This paper discusses characteristics of the seasonal variation in phthalate acid esters (PAEs) in the PM2.5 in the city of Changji, which is located an arid area of Xinjiang Province, northwest China. Samples were collected using a Laoying 2030 median discharge intelligent total suspended particulate (TSP) sampler and analyzed by a Shimadzu GC-2010 gas chromatograph. The results showed that PAEs in PM2.5 were mainly composed of phthalic acid dibutyl phthalate (DBP) and phthalic acid (2-)ethyl hexyl ester (DEHP). DBP and DEHP are the most commonly used plasticizers, accounting for the majority of plasticizers used, and have large environmental emissions. Compared with the proportions of TSPs, proportions of DBP and DEHP in the PM2.5 were lower, while the proportions of DMP and DEP were higher. A correlation exists between the distribution of PAEs and the particle size and concentration of atmospheric particulates. Seasonal variations in DBP and DEHP were the same, with lowest concentrations in the summer. Although seasonal variation in DMP was not the same as those of DBP and DEHP, the general trend was similar. Seasonal variation in DEP was different from those of other PAEs. This pattern is related to PAE characteristics and seasonal variations in their sources.